ASSESSING THE PRODUCTIVE EFFICIENCY AMONG SMALLHOLDER COWPEA FARMERS IN NORTHERN GHANA - Khalid, A-M; Ayamga, M.; Dans-Abbeam, G. (UDS International Journal of Development, 2019)
Understanding the sources and drivers of inefficiency in Ghana’s crop production systems remains an imperative. This study uses stochastic frontier modelling to investigate the technical, allocative and economic efficiency of cowpea production in Tolon, Savelugu-Nanton, and Gushegu districts of the Northern region using cross-sectional data of the 2013/14 cropping season. Technical, allocative, and economic efficiencies averages were estimated to be 91.6%, 80.7%, and 73.4%, respectively. The results suggest that there is enough potential for cowpea farmers to increase production and net profits. The results also show that, quantity of seeds, labour, and farm size exert significant positive effects on the output of cowpea, while expansion in land under cultivation decreases average costs, an observation consistent with economic theory. The study also finds that, education, land ownership, number of years in cowpea farming, and agricultural extension services were the significant determinants of technical inefficiency. The study recommends that farmer education be intensified though well-tailored agricultural extension services. Keywords: Allocative efficiency, Cowpea, Economic efficiency, Northern Ghana, Technical efficiency